Rapid cooling and geospeedometry of granitic rocks exhumation within a volcanic arc: A case study from the Central Slovakian Neovolcanic Field (Western Carpathians) - Kohút, M.; Danišík, Martin (Blackwell Publishing Asia, 2017)
U-Pb Sensitive High-Resolution Ion MicroProbe (SHRIMP) dating of zircon in combination with (U-Th)/He dating of zircon and apatite is applied to constrain the emplacement and exhumation history of the youngest granitic rocks in the Western Carpathians collected in the Central Slovakian Neovolcanic Field. Two samples of diorite from the locality Banky, and granodiorite from Banská Hodruša yield the U-Pb zircon concordia ages of 15.21 ±0.19 Ma and 12.92 ±0.27Ma, respectively, recording the time of zircon crystallization and the intrusions' emplacement. Zircon (U-Th)/He ages of 14.70 ±0.94 (Banky) and 12.65 ±0.61Ma (Banská Hodruša), and apatite (U-Th)/He ages of 14.45 ±0.70Ma (diorite) and 12.26 ±0.77Ma (granodiorite) are less than 1Myr younger than the corresponding zircon U-Pb ages. For both diorite and granodiorite rocks their chronological data thus document a simple cooling process from magmatic crystallization/solidification temperatures to near-surface temperatures in the Middle Miocene, without subsequent reheating. Geospeedometry data suggest for rapid cooling at an average rate of 678 ±158 °C/Myr, and the exhumation rate of 5mm/year corresponding to active tectonic-forced exhumation. The quick cooling is interpreted to record the exhumation of the studied granitic rocks complex that closely followed its emplacement, and was likely accompanied by a drop in the paleo-geothermal gradient due to cessation of volcanic activity in the area.